Quality of Cactus Stems (Opuntia ficus-indica) During Low-Temperature Storage - Rodriguez-Felix, A. (Journal of the Professional Association for Cactus Development, 1997)
The quality of cactus stems (Opuntia ficus-indica) during storage at low temperature was evaluated. Cactus stems of commercial size (selections COPENA F-1 and COPENA V-1) were harvested manually, packed in wooden crates, selected for visual defects, and stored at 5°C, 10°C, and 20°C. Periodically, they were sampled for quality evaluation; measured variables were: color (hue angle), weight loss (%), bending force, texture (as fibrousness), ascorbic acid content, decay, and chilling injury. Color (hue angle) on the day of harvest was 125 (this value is within the green-color area) and did not show marked changes during storage. Weight loss for both selections averaged 12.6% after 9 days at 20°C, 13.8% after 21 days at 10°C, and 14.4% after 21 days at 5°C. The force applied to bend the cactus stems (bending force) decreased during storage, whereas texture showed a variable behavior. Ascorbic acid content decreased during storage at the studied temperatures. Chilling injury was manifested after 15 days at 5°C, and a low incidence of decay was observed. Main quality changes that affected storage life of cactus stems were weight loss and chilling injury.